Analysis of Electromagnetic Transmission through Dielectric filled Apertures of Arbitrary Shape in a Thick Conducting Screen - Abungu, Nicodemous Odero; Konditi, D B O; Otieno, A V (My University, 2005)
The paper deals with an extension of the previous work appearing in a past issue of this transaction by the authors on hybrid FEM/MOM technique for analyzing transmission properties of arbitrarily shaped apertures on a thick conducting screen. In the present work, the effect of placing different dielectric material slabs in the conducting screen cavity on the electromagnetic transmission parameters is first analyzed and, then, the effect of interchanging the positions of these dielectric slabs relative to the incident field. Validation results for rectangular and cross-shaped slots are presented. Close agreement between our data and published data is observed. Further data has been generated for rectangular, circular, diamond-shaped and cross-shaped apertures.
Keywords: Apertures of arbitrary shape; Dielectric-filled cavity; Different Dieletric slabs at arbitrary position; Hybrid FEM-MOM technique; Perfect conducting screen